Resident Support Network: a supportive approach to resident physician wellness - Mazze, Nina; Pavalagantharajah, Sureka; Kwan, Celia; Nieuwesteeg, Alexandra; Young, Claire; Humphreys, Joanna (Canadian Medical Education Journal, 2023)
Implication Statement The Resident Support Network (RSN) is a formal network of residents and medical faculty, with additional training and resources in resident wellness. RSN is accessible to residents to approach with their wellness concerns. It aims to support residents during a period of medical training that is associated with high trainee burnout rates. Implementing individual-focused and organizational strategies in residency programs has been found to reduce burnout. The RSN, in the McMaster University Pediatrics Residency program, was initiated based on the need to help address gaps in supporting resident wellness. Implementation of an RSN would likely provide similar benefits for residents in other universities and specialties by enhancing resident wellness.